Mechanical response of single triacylglycerol spherulites by using microcolloidal probes - Yoshikawa, Hiroshi; Tanaka, Motomu (Chemistry letters, 2017)
First insights into the mechanical properties of a single fat spherulite were obtained by the indentation with microcolloidal probes. We found that the single spherulite of triacylglycerol acts like an elastic body after pushing several times with a microcolloidal probe. The calculated elastic modulus for the single spherulite was comparable with that of condensed triacylglycerol samples, measured using a bulk rheometer, despite an apparent difference in morphology and volume fraction.
Gesehen am 09.08.2018